The nice guys [videorecording (DVD)] - Crowe, Russell, 1964-; Gosling, Ryan, 1980-; Rice, Angourie, 2001-; Bomer, Matthew, 1977- (Warner Home Video, 2016)
In 1970s Los Angeles, down-on-his-luck private eye Holland March and hired enforcer Jackson Healy must work together to solve the case of a missing girl and the seemingly unrelated death of a porn star. During their investigation, they uncover a shocking conspiracy that reaches up to the highest circles of power.